Tuju: Arketipeâ€™s impression of Pakasiah In Music Composition â€œJeratâ€ - Aluna Aluna (Melayu Arts and Performance Journal, 2025)
Pakasiah is one of the mystical phenomena found in the Koto Nan Gadang area, Payakumbuh City. Pakasiah is performed to subdue or conquer a spouse, done by a wife towards her husband. The event of Pakasiah is portrayed in a music compositionÂ  titled 'Jerat' which is developed using a Psychoanalytic approach, where aspects found in the perpetrators involved in the Pakasiah event are concluded, namely the desire and purpose behind performing Pakasiah. This desire is rooted in the human subconscious, like fears, desires, and so on that are embedded within oneself, referred to as shadowâ€™s archetypes. These aspects are then analogized to musical elements that have relevance to works with extra-musical ideas. This music composition is developed through stages including exploration, material identification, and application with an Impressionist musical style approach. Overall, the work Jerat has the structure with the name Tuju, which embodies the archetypal aspect of the performer Pakasiah then developed into a musical composition in ensemble format.